2002
DOI: 10.1046/j.1526-4610.2002.02050.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Menstrually Related Migraine and Nonmigraine Primary Headache in Female Students of Belgrade University

Abstract: The results obtained are in accord with the prevailing opinion that there is a relationship between migraine and female sex hormones, and suggest that women with nonmigraine headache are also susceptible to hormonal fluctuations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 32 publications
5
72
0
3
Order By: Relevance
“…Among 1298 students with headache, 245 had migraine and 1053 had non-migraine headache, the prevalence rates being 12.6% and 54.2%, respectively. Female students with migraine and non-migraine headaches were comparable regarding age (≈22 years), onset of migraine or onset of non-migraine headaches [6].…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Among 1298 students with headache, 245 had migraine and 1053 had non-migraine headache, the prevalence rates being 12.6% and 54.2%, respectively. Female students with migraine and non-migraine headaches were comparable regarding age (≈22 years), onset of migraine or onset of non-migraine headaches [6].…”
Section: Resultsmentioning
confidence: 97%
“…Detailed questions were asked regarding the most severe type of headache: the duration of the headache, the frequency of headache, the average number of headache attacks per month or per year, as well as regarding the duration, location, quality, and intensity of their headache, the influence of physical activity upon their headache, the occurrence of nausea, vomiting, photophobia, or phonophobia, and the occurrence and duration of associated neurological symptoms. The main purposes of the study were to estimate the prevalence of migraine and non-migraine primary headache [6], and at the same time to obtain data about hormonal characteristics and regularity of sleeping, eating and smoking habits. The study was conducted according to the ethical principles established in the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
“…In Oman, in the Persian Gulf, high prevalence rates were observed for headache (98.3% at some moment in life and 96.8% in the latest year of life) among 403 college students, with a mean age of 21.9 years; sd=1.9 and a majority of women (62.5%) (20) . At the University of Belgrade, Yugoslavia, the prevalence of headache among Medicine and Pharmacy college students between 18 and 28 years of age corresponded to 66.8% (10).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown, however, that migraine and tension headache most affect women (6,9-10, 14, 19-20) , leading to the hypothesis that these were the two most frequent types of headache among female college students in this study. Moreover, regarding migraine, an association is observed with the hormonal variations women are subject to in their lifetime, especially related to the menstrual cycle (10) . Besides, the migraine is described as pounding/throbbing and moderate to severe, similar to the present study findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation